Effect of external debt on economic growth in sub-Saharan Africa: System GMM estimation - Isubalew Daba Ayana; Wondaferahu Mulgeta Demissie; Atnafu Gebremeskel Sore (Cogent Economics & Finance, 2023)
Following the upsurge of external debt in SSA countries, the effect of external debt on economic growth has captured the attention of empirical studies during the last two decades of the twenty-first century. This study investigated the short- and long-run effect of external debt on the economic growth of 39 SSA countries during the last decade for the periods of 2011-2021. The annual balanced dynamic panel data for the study were sourced from a recognized trustworthy data source, the world development indicator. The result of the study divulged that external debt has a significant negative impact in both the short and long run. Unequivocally, other things remaining constant, a percentage change in total external debt is associated with a 0.034 percent decline in the real GDP of SSA in the short run, while it leads to 0.65 percent shrinkage in the real GDP of SSA in the long run. The study concludes that the negative impact of the long run is greater than that of the short run. The policy implication is that SSA countries should allocate the external debt on the projects that bring other investment opportunities to amortize external debt. Further, the strategies that improve domestic revenue mobilization sources that compliment external debt such as improving informal sectors to broaden tax bases and minimizing domestic revenue leakages need to be established in SSA countries.
Keywords: 330; external debt and real GDP; panel data; SSA countries; system GMM